Nutritional, chemical and bioactive characterization of Peumus boldus L. - Oliveira, Izamara (2022)
Peumus boldus L. (boldo) is known for its pharmacological effects associated with the chemical composition of its leaves. The objective of this work was to perform the nutritional, chemical and bioactive characterization of boldo leaves. The nutritional profile (crude fat, protein, ash, fiber, and carbohydrates) was determined using AOAC methods [1], while free sugars were determined by HPLC-RI and fatty acids by GC-FID. Moreover, organic acids were determined by HPLC-DAD, tocopherols by HPLC-fluorescence, and phenolic compounds by HPLC-DAD-ESI/MS. Afterwards, a hydroethanolic extract was prepared by maceration (80:20 v/v, ethanol:water), and the antioxidant potential was evaluated using the thiobarbituric acid reactive substances (TBARS) assay; antimicrobial capacity using the microdilution method against pathogenic microorganisms; cytotoxicity against tumor and non-tumor cell lines using the sulforhodamine B assay, and anti-inflammatory potential using RAW cells. For the nutritional profile results, the highest values were obtained for carbohydrates (78 ± 1 g/100 g dw, of which 48.0 ± 0.2 g/100 g dw corresponded to fiber), followed by proteins (8.2 ± 0.5 g/100 g dw), ash (10.0 ± 0.9 g/100 g dw) and fat (4.24 ± 0. 06 g/100 g dw), having an energetic value of 285 ± 2 kcal. Glucose (6.82 ± 0.03 g/100 g dw), followed by fructose (2.70 ± 0.04 g/100 g dw) and sucrose (1.50 ± 0.10 g/100 g dw) were the detected sugars. Ten fatty acids were found, with three main compounds standing out, namely palmitic (29.56 ± 0.05 %), oleic (19 ± 5 %) and linolenic (17 ± 2 %) acids. Five organic acids were identified, highlighting oxalic (1.26 ± 0.04 g/100 g dw) and quinic (1.24 ± 0.05 g/100 g dw) acids. The vitamin E isoforms γ-tocopherol (15 ± 1 g/100 g dw) and α-tocopherol (5.2 ± 0.3 g/100 g dw) were the ones identified in boldo leaves. Seventeen phenolic compounds were detected, from which proanthocyanidins were the most prominent, especially a proanthocyanidin dimer (34.69 ± 0.91 mg/g), and two proanthocyanidin trimers, 1 (32.12 ± 0.75 mg/g) and 2 (18.59 ± 0.67 mg/g). For the antioxidant potential (TBARS), an EC50 of 36.8 ± 0.2 μg/mL was determined, and for the antimicrobial capacity, lower minimum inhibitory concentrations (MIC) were seen especially against the foodborne bacteria Yersinia enterocolitica (1.25 mg/mL) and Staphylococcus aureus (1.25 mg/mL), as well as the clinical isolates E. coli (2.5 mg/mL), Morganella morganii (2.5 mg/mL), Enterococcus faecalis (2.5 mg/mL) and methicillin-resistant S. aureus (2.5 mg/mL). Boldo leaves showed cytotoxicy against nonsmall lung carcinoma (71 ± 4 μg/mL), gastric adenocarcinoma (159 ± 12 μg/mL), and breast carcinoma (280 ± 9 μg/mL) cells. They also showed anti-inflammatory activity for macrophage cell line (RAW cells) at 145 ± 13 μg/mL. Thus, besides being rich in nutrients, P. boldus revealed the presence of bioactive compounds which can be used for future applications in the food, cosmetic and pharmaceutical industries.